Rationality, identity and choice: An ethical criticism of Dr Han Suyin’s autobiography / Florence Kuek Chee Wee - Florence Kuek , Chee Wee (2018)
When China was completely closed to the Western world between during the Cold War, namely, 1947 to 1991, China-born Eurasian author and physician Dr Han Suyin, who became British citizen and Swiss resident, was among the few who were allowed to visit China. Though controversial, her autobiographical accounts regarding 20th century China was quite notable. Her reconstructed modern Chinese history pointed to the birthing of a ―phoenix‖ namely, China, hinting on a new ethical order in East-West relations. Captured in her six-volume autobiography, namely The Crippled Tree series, the East-West conflicts also surfaced in the microcosm of Han Suyin‘s family history as well as her own identity search. Autobiographies are traditionally understood as means of self-redemption or self-validation of the respective autobiographers. In the case of Dr Han Suyin, it was an epistemological means to her self-knowledge and self-assertion. Having rejected her maiden name Rosalie, Han Suyin learned later that she was to embrace her dual-ethnicity after all. The adoption of the Chinese pseudonym ―Han Suyin‖ was one of her efforts to reconstruct her new identity. By revisiting the ethical issues in her family saga as well as the experience of the mixed-race individuals, Han Suyin went through the plethora of taboo, trauma, confusion, multiple ethical choices, plenty of dilemmas and a lifetime of soul-searching for a place where she could be home. The entire process of rejecting ―Rosalie,‖ accepting ―Rosalie‖ and thriving beyond ―Rosalie‖ was, nonetheless, the best reflection of her mode of survival in a series of debatable ethical choices. Moreover, her choices were in stark difference when compared with the choices made by her siblings and her Eurasian peers. This thesis chiefly employs Ethical Literary Criticism (ELC) in examining the various ethical dimensions in Han Suyin‘s autobiographical series.